AN OVERVIEW OF SEXUAL VIOLANCE VICTIMS BASED ON A CONSENSUAL ACT AT THE INTEGRATED CRISIS CENTER CIPTO MANGUNKUSUMO HOSPITAL APRIL 2012 - MARCH 2013 - Syaifuddin, Muhammad Ardhian; Budningsih, Yuli (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
Sexual violance is a widely public concerned criminal act. A serious care and treatment is needed for its victims. Some cases are consensual acts between the perpetrator and the victim and reported by a third party. At the Integrated Crisis Center Cipto Mangunkusumo Hospital, on a period between April 2012 until March 2013, 294 victims of sexual violance including victims of child sexual abuse, rape, adultery, obscenity, and kidnapping of a minor, were examined medico-legally as official requests from the authorities. From those cases, 63 cases or 21,43% are based on a consensual act. The examination process may be more traumatizing then the sexual act itself. Because the victim has the right to refuse the examination process, therefore the examination process must be highly regarding the victim’s honour, moreover the victim’s dignity will remain intact as well as the judicial process.
Keywords: sexual violance, rape, PKT, RSCM